Analisis Peran Pemberdayaan Masyarakat Dalam Pengelolaan Desa Wisata Religi Terhadap Kehidupan Sosial-Ekonomi (Studi Pada Situs Makam K.H. Siradj Payaman, Kecamatan Secang, Kabupaten Magelang) - Alif Muhammad Zakaria; Mauliyana Rachmat (IAIN Salatiga, 2021)
Empowerment and management of religious tourism villages is one alternative to overcome the still high economic and social security in Indonesia, given that the village is the frontline in regional economic development, it is necessary to empower communities to advance the economy and prosperity. This study aims to analyze how the role of empowerment and management of religious tourism villages for the socio-economic life of local communities, this research is qualitative with descriptive analysis methods, while the data from this study are divided into two (2) types, namely primary and secondary. The results of this study indicate that the impact caused is an increase in local community income through MSMEs and increased mutual respect, social service, and mutual cooperation.Keywords: Village, Religious Tourism, Community Empowerment